Abbasid Politics and Performative Panegyric: The Poetry of ʿAli ibn Jabala. (February 2021) - Alebdha, Fahd
Abstract: The poet ʿAli ibn Jabala, also called al-ʿAkawwak, was a little known but significant poet who lived during the late 8th and early 9th centuries. This article examines his poetry in its political and cultural context to delineate the literary devices exploited by the poet in his poems of praise. Moreover, this paper interprets existing prose anecdotes claiming that al-ʿAkawwak's panegyric poem to the caliph al-Maʾmun's commander, Abu Dulaf al-ʿIjli, made the caliph so furious that he ordered the poet's execution, despite the poet having never composed any verses overtly criticizing the caliph. The argument is made that, within the tense political atmosphere of the time, the style that the poet embraced in praising the two commanders, Abu Dulaf al-ʿIjli and Humayd al-Tusi, intensified al-Maʾmun's anger toward the poet.